Productivity and carbon fluxes depend on species and symbiont density in soft coral symbioses - Pupier, Chloé A. (Sci Rep, 2019)
Soft corals often constitute one of the major benthic groups of coral reefs. Although they have been documented to outcompete reef-building corals following environmental disturbances, their physiological performance and thus their functional importance in reefs are still poorly understood. In particular, the acclimatization to depth of soft corals harboring dinoflagellate symbionts and the metabolic interactions between these two partners have received little attention. We performed stable isotope tracer experiments on two soft coral species (Litophyton sp. and Rhytisma fulvum fulvum) from shallow and upper mesophotic Red Sea coral reefs to quantify the acquisition and allocation of autotrophic carbon within the symbiotic association. Carbon acquisition and respiration measurements distinguish Litophyton sp. as mainly autotrophic and Rhytisma fulvum fulvum as rather heterotrophic species. In both species, carbon acquisition was constant at the two investigated depths. This is a major difference from scleractinian corals, whose carbon acquisition decreases with depth. In addition, carbon acquisition and photosynthate translocation to the host decreased with an increase in symbiont density, suggesting that nutrient provision to octocoral symbionts can quickly become a limiting factor of their productivity. These findings improve our understanding of the biology of soft corals at the organism-scale and further highlight the need to investigate how their nutrition will be affected under changing environmental conditions.